(untitled) (Revista Rupturas, 2025)
This article addresses the relationship between soccer gender and the sports press by analyzing the information coverage of the so-called Rubiales case in Costa Rica, to evaluate the journalistic treatment of cases of sexual violence and coercion against women, specifically in the sports field, from a gender perspective. A qualitative approach is developed through the execution of a case study design from a gender perspective. The data collection technique was the documentary review, and a content analysis was carried out. The results show that, in the case of this study, the male subject is the configuring entity of the story, so it is concluded that in this case, for everything described, it can be said that a news coverage lacking a gender perspective predominated, based on the male figure as a reference to communicate what happened and focused on relativizing the denounced events. Therefore, hegemonic representations about what happened were consolidated using mechanisms of exclusion and female invisibility, which constitutes a case of media violence framed in the moral violence historically exercised against women.